National register of doctoral dissertations accepted & in progress in social sciences and humanities in Indian universities, humanities - Shanker, Laxmi; Ḥāmid Ḥusain, Sayyid (Publications Division, Council of Oriental Research, 1979)
Project undertaken by the Council of Oriental Research, Bhopal; covers research done up to 1978 and subjects registered since 1970.